Partial pressure (or fugacity) of carbon dioxide, salinity and other variables collected from Surface underway observations using Carbon dioxide (CO2) gas analyzer, Shower head chamber equilibrator for autonomous carbon dioxide (CO2) measurement and other instruments from the KNORR in the North Atlantic Ocean from 2011-06-28 to 2011-07-13 (NCEI Accession 0117690) ... - Ward, Brian; Almeida, Joao (NOAA National Centers for Environmental Information, 2014)
This dataset includes Surface underway, chemical, meteorological and physical data collected from KNORR in the North Atlantic Ocean from 2011-06-28 to 2011-07-13 and retrieved during cruise 316N20110628. These data include BAROMETRIC PRESSURE, Partial pressure (or fugacity) of carbon dioxide - atmosphere, Partial pressure (or fugacity) of carbon dioxide - water, SALINITY and SEA SURFACE TEMPERATURE. The instruments used to collect these data include Carbon dioxide (CO2) gas analyzer and Shower head chamber equilibrator for autonomous carbon dioxide (CO2) measurement. These data were collected by Brian Ward of National University of Ireland - Galway as part of the VOS_BLOOMCRUISE_2011 dataset. ...